Traumatic Brain Injury Induces cGAS Activation and Type I Interferon Signaling in Aged Mice - Barrett, James P.; Knoblach, Susan M.; Bhattacharya, Surajit; Gordish-Dressman, Heather; Stoica, Bogdan A.; Loane, David J. (Frontiers in Immunology, 2021)
Aging adversely affects inflammatory processes in the brain, which has important implications in the progression of neurodegenerative disease. Following traumatic brain injury (TBI), aged animals exhibit worsened neurological function and exacerbated microglial-associated neuroinflammation. Type I Interferons (IFN-I) contribute to the development of TBI neuropathology. Further, the Cyclic GMP-AMP Synthase (cGAS) and Stimulator of Interferon Genes (STING) pathway, a key inducer of IFN-I responses, has been implicated in neuroinflammatory activity in several age-related neurodegenerative diseases. Here, we set out to investigate the effects of TBI on cGAS/STING activation, IFN-I signaling and neuroinflammation in young and aged C57Bl/6 male mice. Using a controlled cortical impact model, we evaluated transcriptomic changes in the injured cortex at 24 hours post-injury, and confirmed activation of key neuroinflammatory pathways in biochemical studies. TBI induced changes were highly enriched for transcripts that were involved in inflammatory responses to stress and host defense. Deeper analysis revealed that TBI increased expression of IFN-I related genes (e.g. Ifnb1, Irf7, Ifi204, Isg15) and IFN-I signaling in the injured cortex of aged compared to young mice. There was also a significant age-related increase in the activation of the DNA-recognition pathway, cGAS, which is a key mechanism to propagate IFN-I responses. Finally, enhanced IFN-I signaling in the aged TBI brain was confirmed by increased phosphorylation of STAT1, an important IFN-I effector molecule. This age-related activation of cGAS and IFN-I signaling may prove to be a mechanistic link between microglial-associated neuroinflammation and neurodegeneration in the aged TBI brain.